Inter and Intra-rater Reliability of Lateral Cephalometric Analysis Using 2D Dolphin Imaging Software: Reliability of Lateral Cephalometric Analysis Using 2D Dolphin Software - Khosravani, Sarvin; Esmaeili, Saharnaz; Malek Mohammadi, Nazanin; Eslamian, Ladan; Dalaei, Kazem; Motamedian, Saeed Reza (Journal of Dental School, 2021)
Objectives Cephalometric radiographs are widely used in diagnosis and treatment planning. In the past, these radiographs used to be analyzed manually, but nowadays due to the possibility of errors and time-consuming nature of manual tracing, digital methods are replacing the manual methods. The reliability of computer-assisted analysis is of great importance. The purpose of this study was to investigate the inter and intra-rater reliability of 2D Dolphin imaging software version 10.0.00.53. Methods To assess the intra-rater reliability of lateral cephalometric analysis, 25 lateral cephalograms traced by one operator using Dolphin imaging software were traced again by the same examiner 2 weeks later. To assess the inter-rater reliability, 25 lateral cephalograms were traced independently by two examiners. Overall, 80 measurements including 43 linear, 34 angular, and 3 ratio measurements were made. The interclass correlation coefficient (ICC) was calculated to assess the inter-rater and intra-rater reliability. ICCs above 0.75 were considered good. Results The ICC for intra-rater reliability was above 0.75 for all parameters except lower vertical height depth ratio (ICC=0.51), inter-labial gap (ICC=0.54), superior sulcus depth (ICC=0.67), articular angle (ICC=0.733), and ramus height (ICC=0.728). The ICC for inter-rater reliability was above 0.75 for all parameters except nose prominence (ICC=0.73). Conclusion Dolphin imaging software showed good intra-rater reliability for most parameters and good inter-rater reliability for almost all parameters.